2010
DOI: 10.2989/18142321003714302
|View full text |Cite
|
Sign up to set email alerts
|

Exploring basic biochemical constituents in the body tissues of South African abaloneHaliotis midaereared in shore-based mariculture systems

Abstract: The study quantifies the effects of season, age and feeding regime on glucose, glycogen, proteins and lipids in abalone Haliotis midae tissues, and to assess water loss during simulated live export. Abalone of two age classes, younger (~30 months old) and older (~38 months old), were subjected to four dietary regimes: two single feeds, kelp and an artificial feed, and two rotational feeding regimes utilising kelp and the artificial feed in varying ratios. Total protein, free glucose, glycogen and total lipid c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(14 citation statements)
references
References 31 publications
1
13
0
Order By: Relevance
“…Research done on plants show that during stress, proline and lipid metabolism share dual roles (Shinde, Villamor, Lin, Sharma, & Verslues, ), suggesting that proline has the ability to regulate β‐oxidation, subsequently resulting in decreased acetylcarnitine and an increase in alanine, as seen in this experiment (Figure ). Furthermore, adult abalone have the capacity to accumulate lipid stores, suggesting an increased dependence on a pathway like β‐oxidation for energy production in H. midae (Laas & Vosloo, ). Based on a dietary lipid investigation conducted on H. iris, it was concluded that lipids do not significantly affect the growth of this abalone species (Tung & Alfaro, ), which could be true for H. midae as well.…”
Section: Discussionmentioning
confidence: 99%
“…Research done on plants show that during stress, proline and lipid metabolism share dual roles (Shinde, Villamor, Lin, Sharma, & Verslues, ), suggesting that proline has the ability to regulate β‐oxidation, subsequently resulting in decreased acetylcarnitine and an increase in alanine, as seen in this experiment (Figure ). Furthermore, adult abalone have the capacity to accumulate lipid stores, suggesting an increased dependence on a pathway like β‐oxidation for energy production in H. midae (Laas & Vosloo, ). Based on a dietary lipid investigation conducted on H. iris, it was concluded that lipids do not significantly affect the growth of this abalone species (Tung & Alfaro, ), which could be true for H. midae as well.…”
Section: Discussionmentioning
confidence: 99%
“…). Poor perfusion, high glycogen reserves (Laas & Vosloo ) and the diversity in anaerobic enzymes (Gäde ; O'omolo et al . ) suggest that the foot muscle relies primarily on anaerobic glycolysis for energy generation.…”
Section: The Interrelationship Between Structure Function and Metabomentioning
confidence: 99%
“…). Due to these dynamic functions, biochemical constituents of the digestive gland tissue are highly variable (Laas & Vosloo ), and there have been conflicting reports of digestive gland glycogen decreasing (Carefoot et al . ) or remaining unchanged (Sheedy et al .…”
Section: The Interrelationship Between Structure Function and Metabomentioning
confidence: 99%
See 2 more Smart Citations